Social Perspectives of Pedagogy: Moral Behavior of Learners in Primary Schools - Fitriyani; Arifin Maksum; Nina Nurhasanah; Yuli Rahmawati (Westscience Press, 2023)
The phenomenon that currently occurs a lot is social interaction which results in moral degradation in elementary schools occurs because it is caused by a decrease in the moral value of students in school, this currently occurs a lot in the routine every day at school. Interactions that occur in schools can be formed due to 2 things, namely social contact and communication between students and friends, teachers, and the community around the school. This paper is aimed at knowing the views of the social perspective of pedagogy that influence the moral behavior and character of learners in elementary school. Human behavior in the perspective of social psychology will relate to behavioral perspectives, cognitive perspectives, structural perspectives and interactionist perspectives as an understanding of human behavior. This research uses a qualitative approach with ethnographic methods. This research was conducted in Cikarang, Indonesia. Based on the results of research on the social pedagogical perspective of students at SDN Cipayung 05 Cikarang at a level that really needs focus and guidance by the school with the help of supervision from parents of students of SDN Cipayung 05 Cikarang.